Numerical simulation study on temperature field of ice slurry pre-cooled broccoli - LI Gan; WANG Qing; LU Li-xin; PAN Liao (Shipin yu jixie)
Objective: In order to solve the problem of complicated state in the process of pre-cooling packaging of fluid ice, it provides a basis for the application of fluid ice in the storage and transportation of fruits and vegetables, fresh-keeping and so on. Methods: Taking broccoli as the research object, the heat transfer model of pre-cooling broccoli with fluidized ice was established. The change of temperature field and ice crystal particles during the process of precooling and storage of broccoli was simulated by CFD. The effects of fluid ice crystal integral number and mass ratio of fluid ice on broccoli precooling and storage temperature were analyzed, and the verification experiment was carried out. Results: The larger the volume fraction of ice crystal, the more uniform the distribution of ice crystal particles and the better the precooling uniformity; When the mass ratio of fluidic ice was 100%, the fluidic ice could meet the requirement of precooling temperature. Conclusion: By adjusting the volume fraction and mass ratio of fluid ice and reducing the redundancy of the upper space inside the packaging, the pre-cooling effect of broccoli can be improved and the storage time can be extended.